Quad-qualified audit committee director: Implications for monitoring and reducing financial corruption - Gorshunov, Mikhail A.; Armenakis, Achilles A.; Harris, Stanley G.; Walker, H. Jack (Journal of Corporate Finance, 2021)
Financial corruption has an extensive adverse impact on corporate stakeholders. Over the last two decades, numerous prescriptions have been offered to improve the governance of US public firms, yet financial corruption is still prevalent. Board of directors' audit committees are typically charged with the responsibility of assuring that the corporation's financial reports satisfy the criterion of accuracy. We propose that a quad-qualified audit committee director can serve as an exemplar corporate overseer of financial reporting and minimize the likelihood of corruption. We predict that by having the qualifications of independence, directorship experience and financial expertise, bandwidth, and stock ownership, the effectiveness of monitoring financial reporting by such a director will be considerably enhanced, thus complementing the benefits of the US Sarbanes-Oxley Act (SOX) enacted in 2002. To test our predictions, we employed a time-lagged, matched-pairs sample of 328 large US corporations (164 financially corrupt firms plus a comparison group of 164 compliant firms). Controlling for covariates, we found that the presence of a quad-qualified audit committee director reduced the likelihood of financial corruption in a public firm by 72%. Combined with the benefits from SOX, having at least one quad-qualified audit committee director decreased the probability of financial corruption by 92%. Our results also show that having just one quad-qualified audit committee director is more effective than the combination of the individual qualifications dispersed among the committee members.